Akibat Hukum Pengangkatan Pembina Yayasan oleh Pengurus dan Pengawas yang sudah Berakhir Masa Jabatannya - Nusa, Luh Putu Ayu Meilina Melati Putri; Djumikasih, Djumikasih; Widhiawati, Dyah (Universitas Negeri Malang, 2023)
The aim of writing the article is to discuss the legal consequences of appointing foundation supervisors by administrators and supervisors whose terms of office have ended. This study is socio legal research using a socio-legal approach. Data collection techniques used interviews and documentation studies, data analysis used qualitative descriptive analysis. The management and supervisors who appointed the supervisors have had their term of office expired so they do not have the authority to make the appointment. The legal consequences that occur are that the position is invalid, the supervisor does not have authority, the legal action taken is invalid, can be sued if someone is harmed, the meeting decision statement is not an authentic deed, personally responsible if there is loss. The appointment of supervisors is in accordance with organ theory, namely that the appointment of supervisors is necessary because they are the highest organ in the foundation and have an important role in making various decisions. Appointment is contrary to the theory of attributive authority and legal certainty. The issuance of a Decree from the Ministry of Law and Human Rights is the reason to justify the validity of the appointment of foundation supervisors. Abstrak: Artikel ini bertujuan memb